A Practical Protocol for the Conjugation of Various Amino Acids to Protoporphyrin IX - Maximova, Ksenia; Pisarek, Sabina; Gryko, Dorota (Synthesis, 2013)
An effective and reliable method was developed for the synthesis of protoporphyrin IX-derived amides. The reaction of protoporphyrin IX with an amino acid [l-leucine, l-valine, l-lysine, l-aspartic acid (Asp), l-glutamic acid (Glu), glycine, or 6-aminohexanoic acid] or a short peptide (Asp-Glu) as an amine counterpart in the presence of O-(benzotriazol-1-yl)-N,N,N′,N′-tetramethyluronium hexafluorophosphate and 1H-1,2,3-benzotriazol-1-ol gave the desired diamides in excellent yields.
Keywords: porphyrins; amides; amino acids; peptides; esters; hydrolysis